KORELASI GAYA BELAJAR DENGAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPA DI SD NEGERI 3 MUNTOK - Artika Hikmawati; Yuanita; M. iqbal Arrosyad (STKIP Subang, 2026)
This study is predicated on the observed variations in learning styles among students during the educational process. Such differences in learning preferences are posited to impact students’ comprehension of instructional materials and consequently, thei academic achievement. Accordingly, the objective of this research is to examine the correlation between learning styles and the academic outcomes of fourth-grade students in science at SD Negeri 3 Muntok. A quantitative approach employing a correlational research design was utilized in this study. The sample comprised 21 students from class IV B at SD Negeri 3 Muntok. Data collection instruments included questionnaires to identify students’ learning styles, classroom observations to corroborate findings regarding learning preferences, and documentation of learning outcomes through students’ Final Semester Examination (UAS) scores. Data analysis involved the application of normality and linearity tests, and Pearson Product-Moment correlation analysis, conducted using IBM SPSS 26 software. The result of the data analysis shows that the correlation coefficient for visual learning style is 0,525, auditory learning style is 0,518, and kinesthetic learning style is 0,455, indicating thas all three learning styles have a positive correlation between learning style and students’ learning outcomes. Thus, it can be concluded that there is a significant correlation between learning styles and the learning outcomes of fourth-grade students in science subjects at SD Negeri 3 Muntok, with the visual learning style having the highest correlation compared to the auditory and kinesthetic learning styles.